2016
DOI: 10.4172/2153-2435.1000481
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Isotopic Abundance Ratio in Biofield Energy Treated Resorcinol Using Gas Chromatography-Mass Spectrometry Technique

Abstract: The stable isotope ratio analysis is widely used in several scientific fields such as agricultural, food authenticity, biochemistry, metabolism, medical research, etc. Resorcinol is one of the most versatile chemicals used for the synthesis of several pharmaceuticals, dyes, polymers, organic compounds, etc. The current research work was designed to investigate the impact of the biofield energy treatment on the isotopic abundance ratios of 13 C/ 12 C or 2 H/ 1 H or 17 O/ 16 O (P M+1 /P M) and 18 O/ 16 O (P M+2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…The calculated isotopic abundance of P M+1 value 24.24% was higher to the experimental value (16.1%) (Table 1). From the above calculation, it has been found that 13 C and 15 N have the major contribution to m/z 442.92. The LC-MS based isotopic abundance ratio analysis P M and P M+1 for folic acid at m/z 441.92 and 442.92, respectively of both the samples, which were obtained from the observed relative peak intensities of [M + ] and [(M+1) + ] peaks, respectively in the ESI-MS spectra (Table 1).…”
Section: Liquid Chromatography-mass Spectrometry (Lc-ms)mentioning
confidence: 90%
See 3 more Smart Citations
“…The calculated isotopic abundance of P M+1 value 24.24% was higher to the experimental value (16.1%) (Table 1). From the above calculation, it has been found that 13 C and 15 N have the major contribution to m/z 442.92. The LC-MS based isotopic abundance ratio analysis P M and P M+1 for folic acid at m/z 441.92 and 442.92, respectively of both the samples, which were obtained from the observed relative peak intensities of [M + ] and [(M+1) + ] peaks, respectively in the ESI-MS spectra (Table 1).…”
Section: Liquid Chromatography-mass Spectrometry (Lc-ms)mentioning
confidence: 90%
“…The isotopic abundance ratio of P M+1 /P M ( 2 H/ 1 H or 13 C/ 12 C or 15 N/ 14 N or 17 O/ 16 O) in the treated folic acid was significantly increased by 81.37% compared with the control sample. Hence, the 13 C, 2 H, 15 + to m/z 442.92 in the treated sample were significantly increased compared with the control sample.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…The bioavailability of any compound is highly influenced by its physicochemical properties that could be altered to improve its solubility, dissolution, and absorption within the body [20] , and thereby to attain the maximum biological activities [21] . Consciousness Energy Healing Treatment is one among such novel approaches that showed its significant role in modifying the physicochemical and thermal properties of various compounds [22,23] . The use of Energy therapy such as, the Biofield Energy Treatment, against various diseases has been evident now a days as it was found to have advantageous effect and therefore, accepted by the National Center for Complementary and Alternative Medicine (NCCAM) under the field of Complementary and Alternative Medicine (CAM) therapies along with homeopathy, yoga, meditation, acupressure, acupuncture, healing touch, relaxation techniques, hypnotherapy, Pilates, Reiki, Ayurvedic medicine, cranial sacral therapy, traditional Chinese herbs and medicines, etc [24,25] .…”
Section: Introductionmentioning
confidence: 99%